2021
DOI: 10.3390/en14248481
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Advantages of the Separated Electric Compound Propulsion System for CNG Hybrid Vehicles

Abstract: As is widely known, internal combustion engines are not able to complete the expansion process of the gas inside the cylinder, causing theoretical energy losses in the order of 20%. Several systems and methods have been proposed and implemented to recover the unexpanded gas energy, such as turbocharging, which partially exploits this energy to compress the fresh intake charge, or turbo-mechanical and turbo-electrical compounding, where the amount of unexpanded gas energy not used by the compressor is dedicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Considering the isentropic transformation, the static pressure at nozzle outlet was evaluated as: (13) where the isentropic enthalpy drop is obtained as the sum of the actual enthalpy drop (Equation ( 12)) and the volute loss (Equation ( 7)):…”
Section: Analysis Of the Volutementioning
confidence: 99%
See 3 more Smart Citations
“…Considering the isentropic transformation, the static pressure at nozzle outlet was evaluated as: (13) where the isentropic enthalpy drop is obtained as the sum of the actual enthalpy drop (Equation ( 12)) and the volute loss (Equation ( 7)):…”
Section: Analysis Of the Volutementioning
confidence: 99%
“…Moreover, since the rotational speed of the turbine is independent from the engine and from the compressor, it can be optimally controlled and set to the best value acting through the connected generator. In their preliminary studies [13,14], the authors demonstrated that this system is very promising, as it may achieve overall vehicle efficiency advantages up to 15% with respect to a reference hybrid propulsion system of the same nominal overall output power (73.5 kW) equipped with a traditional turbocharged engine. Furthermore, the authors showed that the contribution of the turbogenerator may reach an impressive 33.9% share of the total power generated by the whole system, with maximum power delivered of 20 kW; in this regard, it must be pointed out that in their previous works, the exhaust gas turbine considered was supposed to be optimized for steady-state operation, since in a hybrid propulsion system the thermal engine undergoes small speed and load variations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are higher than the efficiency of turbines commonly used for turbocharging, on account of the more favorable working condition already mentioned, which allows a design strategy for the best efficiency under steady operation, and also permits the electric generator to control the turbine speed of rotation, maximizing its efficiency, apart from the power produced. Some preliminary evaluations made by the same authors [2][3][4] showed that the separated electric compound engine has good potential, since vehicle fuel economy increments up to 15% may be obtained in comparison to a reference hybrid propulsion system endowed with a traditional turbocharged engine with equal maximum output power (73.5 kW). It was also found that the turbo-generator could contribute to vehicle traction by about 34% of the overall power generated for the propulsion, with a maximum delivered power of about 20 kW.…”
Section: Introductionmentioning
confidence: 99%